Review: The ovarian follicular reserve – implications for fertility in ruminants - F. Mossa; A.C.O. Evans (Animal, 2023)
Ruminants are born with a finite number of healthy ovarian follicles and oocytes (ovarian reserve) and germ cell proliferation in the developing foetal gonad predominantly occurs during early gestation. Two markers have been established to reliably estimate the size of the ovarian reserve in cattle: the number of antral follicles ≤3 mm in diameter recruited per follicular wave (Antral Follicle Count, AFC) and peripheral concentrations of the Anti-Müllerian hormone (AMH). Studies that used one or both indicators show that the size of ovarian reserve varies greatly among age-matched individuals, but is highly repeatable in the same animal. Conditions during prenatal life are likely among the causes of such variation in the ovarian reserve. In addition, the size of the ovarian reserve is a moderately heritable trait in cattle. The association between ovarian reserve and fertility is controversial. Several studies indicate that cattle with a low ovarian reserve have phenotypic characteristics that are associated with suboptimal fertility. On the contrary, the presence and absence of a positive association between AFC and/or AMH and fertility measures (i.e. no. on services/conception, pregnancy rates, pregnancy loss) have been equally reported in cattle. In conclusion, the size of the ovarian reserve in the progeny can be enhanced by improving management of the dam from preconception to early gestation and also through genetic selection. However, although the ovarian reserve may be among the determinants of reproductive success in ruminants, the use of AFC/AMH as reliable predictors of fertility is yet to be established. Furthermore, the possibility that there is a complex interaction of AFC, AMH and reproduction has yet to be fully characterised and exploited to improve fertility in cattle.